Clinical and Radiological Markers of Extra-Motor Deficits in Amyotrophic Lateral Sclerosis - Christidi, Foteini; Karavasilis, Efstratios; Rentzos, Michail; Kelekis, Nikolaos; Evdokimidis, Ioannis; Bede, Peter (Frontiers in Neurology, 2018)
Amyotrophic lateral sclerosis (ALS) is now universally recognised as a complex multisystem disorder with considerable extra-motor involvement. The neuropsychological manifestations of frontotemporal, parietal and basal ganglia involvement in ALS have important implications for compliance with assistive devices, survival, participation in clinical trials, caregiver burden, and the management of individual care needs. Recent advances in neuroimaging have been instrumental in characterising the biological substrate of heterogeneous cognitive and behavioural deficits in ALS. In this review we discuss the clinical and radiological aspects of cognitive and behavioural impairment in ALS focusing on the recognition, assessment, and monitoring of these symptoms.